Students’ satisfaction and intention to continue online learning during the Covid-19 pandemic - Siti Ngayesah Ab Hamid; Hafizah Omar Zaki; Zizah Che Senik (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Covid-19 pandemic has forced teaching and learning to be conducted online. Without proper preparation, students and academicians face various challenges, which may cause stress and drop out. Thus, this study was conducted to determine factors influencing students’ satisfaction and intention to continue studying online. Three factors were hypothesized to influence satisfaction, namely the lecturer’s performance, students’ interaction, and course content. The study also examined the moderating role of internet connection on the relationship between satisfaction and continuance intention. Using purposive sampling, data were collected from undergraduate and postgraduate students. A total of 305 questionnaires were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The result of the analysis indicated that all three proposed factors are significant in influencing students’ satisfaction, and satisfaction impacts continuance intention. Internet connection on the other hand moderates the relationship between satisfaction and intention. These findings have broadened the knowledge on the factors of students’ satisfaction and continuance intention to study online during the pandemic. This study is among a limited number of studies available exploring the role of internet connection in the context of online learning. The study provides insights to academicians, higher learning institutions and policymakers on the continuance of online learning during and post-pandemic.